Psychological compatibility and its relationship with self-efficacy in women with breast cancer (Journal of Hama University, 2021)
Introduction: Breast cancer is a threat situation to women’s life and happiness, and the treatment has progressed, It led to their high rates of survival rate, thus, it made them face its negative effects on all aspects of their lives, which may negatively affect their psychological compatibility and self- efficacy, given the importance of these two dimensions in their lives. Purpose: the aim of this study was to identify the level of psychological compatibility and self-esteem in women with breast cancer. Methods: A descriptive correlation study was performed using a sample of 100 women with breast cancer at the Oncology Center at Tishreen University Hospital in Lattakia, Syria. Data was collected by using two pre-set measures of psychological compatibility and self-efficacy was completed. Results The finding showed that the level of general psychological compatibility and the level of self-efficacy were average among the higher percentage of women in the study, and there was a significances positive correlation between psychological compatibility and self-efficacy among them. Recommends: The study recommended to designing educational programs on ways to cope with breast cancer, providing them with sufficient information about the course of the disease and treatment plan, providing them with family and psychological support, and providing means to improve their body image, and conducting a study on the impact of stress during the disease on the level of psychological compatibility and self-efficacy.